ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЛАРЫНДА ПЕРЗЕНТСИЗЛИК МОТИВИНИҢ ГЕЙПАРА ӨЗГЕШЕЛИКЛЕРИ - Исаков, Р.У. (ILIM hám JÁMIYET, 2022)
The article discusses the features of the motif of childlessness in the Karakalpak folk epics. As a source, scientific ideas related to the motif of childlessness in the folklore samples of theTurkic peoples were used.